Physical characteristics as indicators of performance in young alpine skiers in Super-G - Puhalj, Stojan; Lešnik, Blaž; Matejek, Črtomir; Fošnarič, Samo; Kmet, Tjaša; Planinšec, Jurij (Annales Kinesiologiae, 2025)
Purpose: The aim of this study is to determine the relationship between physical characteristics and performance in young alpine skiers in the Super-G discipline. Methods: A sample of 42 U16 alpine skiing competitors (23 boys and 19 girls) aged 14-15 years participated in the study. The physical characteristics were measured using the Inbody 720 Body Composition Analysis and 3D Body Scan devices. Performance data was obtained from official records of the Ski Association of Slovenia for the 2018/19 U16 competitive season. Variables such as body height, body weight, thigh circumference, waist circumference, chest circumference, shoulder circumference, muscle mass percentage, fat mass percentage, body mass index, and body fat percentage were analyzed. Pearson correlation coefficients and multiple regression analysis were used to assess the relationship between the physical characteristics and Super-G performance. Results: Significant correlations were found between body weight, thigh circumference, chest circumference, muscle mass percentage, and Super-G performance in boys. For girls, waist circumference, chest circumference, and body fat percentage were significantly correlated with performance. The multiple regression model explained 73% of the variance in the boys' performance and 59% in the girls', although the model itself was not statistically significant for predicting performance. Conclusion: Physical characteristics, especially muscle mass percentage and body circumferences, are significantly associated with Super-G performance in young alpine skiers. These findings underscore the importance of tailored training programs that consider individual physical characteristics to optimize competitive success in alpine skiing.